Compartment syndrome as reperfusion injury following thrombectomy in acute limb ischemia: A case report - Afifuddin, Mokhammad; Kurnianingsih, Novi; Kurniawan, Dea (Deka in Medicine, 2024)
BACKGROUND: Compartment syndrome following reperfusion in acute limb ischemia represents a rare but serious complication. Thus, documenting such cases is essential to enhance comprehension and management of this condition. CASE PRESENTATION: A 51-year-old man was referred from an urban hospital presenting with severe right leg pain persisting for 5 days prior to admission, accompanied by pulselessness, paresthesia, poikilothermia, and paralysis. The patient had underlying risk factors including uncontrolled diabetes mellitus and active smoking. Duplex ultrasound confirmed the diagnosis of acute limb ischemia, which was further supported by CT angiography revealing total occlusion from the right common iliac artery to the distal region. Intravenous heparin was administered, and the patient underwent emergency surgical thrombectomy. Following the intervention, the patient developed clinical signs of compartment syndrome as a manifestation of reperfusion injury, necessitating fasciotomy. Subsequent evaluation of the wound post-fasciotomy indicated it was not suitable for closure, and unfortunately, the patient passed away a few days later. CONCLUSION: This case illustrates acute limb ischemia necessitating thrombectomy and surgical fasciotomy due to compartment syndrome resulting from reperfusion injury, emphasizing the importance of rigorous monitoring.